Hierarchically assembled carbon microtube@SiC nanowire/Ni nanoparticle aerogel for highly efficient electromagnetic wave absorption and multifunction. (May 2022) - Cai, Zhixin; Su, Lei; Wang, Hongjie; Xie, Qiang; Gao, Hongfei; Niu, Min; Lu, De
Abstract: Efficient electromagnetic wave (EMW) absorption is of great significance to enjoy the service of electromagnetic wave technologies safely. Compared with powder-based EMW absorption materials, aerogels with 3D continous and highly porous network structure have demonstrated to have coordinate impedance matching and attenuation characteristics. Further introducing multicomponent to fabricate aerogels with synergetic conductive/dielectric/magnetic properties are expected to achieve efficient EMW absorption property but still remain challenging. Herein, we report the preparation and properties of a carbon microtube (as conductive network), SiC nanowires (as dielectric network), and Ni nanoparticles (as magnetic network) assembled aerogel with hierarchically network structure that is assembled by. The carbon microtube@SiC nanowire/Ni nanoparticle aerogel displays low density (∼5 mg/cm 3 ), broad absorption bandwidth (10.1 GHz) and strong reflection loss (−51.3 dB). The unique synergistic magnetic/dielectric/conductive coupling attenuation mechanisms contribute to the good EMW absorption performance. This study opens a pathway for using 3D hierarchically network structure with conductive/dielectric/magnetic components to achieve excellent EMW absorption for promising applications. Graphical abstract: Image 1 Highlights: 3D hierarchically network-structured CMT@SiCNW/Ni aerogel is designed and prepared for efficient EMW absorption. The good EMW absorption performance is attributed to unique synergistic magnetic/dielectric/conductive coupling attenuation mechanisms. The aerogel shows self-cleaning, thermal insulation, infrared and visible stealth capabilities.